Considerations on technology and teachers : the best of JRTE - Harris, Judith B.; Inman, John G.; Koehler, Matthew; MacGregor, S. Kim; Mishra, Punya; Schrum, Lynne (Eugene, Oregon International Society for Technology in Education, 2010)
Research offers a way to start conversations that can affect educational reform. Considerations on Technology and Teachers is a collection of some of the best research articles from the Journal of Research on Technology in Education (JRTE) over the past five years. JRTE editor Lynne Schrum and the editorial review board chose these articles because they provide context about where we have been and how we should be moving forward, both in research and in practice. Topics include the impact of project-based learning on teachers technology use, e-portfolios in teacher education, and the outcomes of a campus 1-to-1 laptop program. At the conclusion of each article, the original authors reflect on their study, examine the landscape since their research was published, and provide suggestions for further study.
La función de los autores fue determinada por el catalogador
Keywords: ENSEÑANZA CON AYUDA DE COMPUTADORAS; TECNOLOGÍA EDUCATIVA; INTERNET EN EDUCACION; EDUCACION A DISTANCIA